2016
DOI: 10.18632/oncotarget.10123
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic adenocarcinoma up-regulated factor (PAUF) enhances the accumulation and functional activity of myeloid-derived suppressor cells (MDSCs) in pancreatic cancer

Abstract: Pancreatic cancer is characterized by an immunosuppressive tumor microenvironment (TME) with a profound immune infiltrate populated by a significant number of myeloid-derived suppressor cells (MDSCs). MDSCs have been increasingly recognized for their role in immune evasion and cancer progression as well as their potential as a target for immunotherapy. However, not much is known about the mechanisms regulating their behavior and function in the pancreatic TME. Here we report that pancreatic adenocarcinoma up-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Song et al . reported that PAUF enhances accumulation of tumor-infiltrating Myeloid-derived suppressor cells and its immune suppressive function via TLR4-mediated signaling pathway in PAUF-overexpressing tumor cell-injected mice 39 . With further studies, specific activation or repression of PAUF/TLRs can be harnessed to offer novel immunotherapies or adjuvants to traditional chemotherapy for some ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al . reported that PAUF enhances accumulation of tumor-infiltrating Myeloid-derived suppressor cells and its immune suppressive function via TLR4-mediated signaling pathway in PAUF-overexpressing tumor cell-injected mice 39 . With further studies, specific activation or repression of PAUF/TLRs can be harnessed to offer novel immunotherapies or adjuvants to traditional chemotherapy for some ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other soluble factors that have been associated with the recruitment of MDSCs by pancreatic cancer cells include granulocyte/macrophage colony-stimulating factor (GM-CSF) [ 174 ] and pancreatic adenocarcinoma upregulated factor (PAUF), a soluble protein previously implicated in pancreatic cancer metastasis [ 175 ]. PAUF has been suggested to attract MDSCs to tumor sites in an SDF-1-dependent manner by upregulating the expression of CXCR4 on MDSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of BMDMs, stimulated by NTC-Ms, to induce apoptosis of activated T cells was suppressed by an inhibitor of TRIF pathway [ 65 ], suggesting that TLR4 ligands in NTC-Ms aroused the apoptosis-inducing capability of Gr-1+CD11b+F4/80+ BMDMs, which was further confirmed by the use of sTLR4 expression vector in palpable tumor [ 64 ]. PAUF, a soluble protein involved in pancreatic tumorigenesis and metastasis, interacted with TLR4 on the surface of MDSCs and enhanced their immunosuppressive effects on activated T cells in tumor microenvironment [ 66 ]. Furthermore, wilde et al have found that repetitive injections of LPS induced a cluster of MDSC-like cells, which mediate suppression of T cell response on vitro [ 67 ].…”
Section: Introductionmentioning
confidence: 99%